Experiences and challenges of parents caring for children with attention-deficit hyperactivity disorder: A qualitative study in Dar es salaam, Tanzania - Charles Daud Ching’oma; Dickson Ally Mkoka; Joel Seme Ambikile; Masunga Kidula Iseselo (PLoS ONE, 2022)
Background Attention-deficit hyperactivity disorder (ADHD) is the most common neurobehavioral childhood disorder. Children with ADHD are difficult to handle due to the symptoms causing great impairments such as inattention, hyperactivity compared to other childhood mental disorders. Having a child with ADHD is a stressful situation as it impacts the whole family. However, little is known about the experiences and challenges of parents caring for children with ADHD in low and middle-income countries such as Tanzania. Thus, this study explored the experiences and challenges of parents caring for children with ADHD in Dar es Salaam, Tanzania. Methods We conducted a qualitative descriptive study involving 16 parents of children with ADHD at Muhimbili National Hospital (MNH). We used the purposive sampling technique to obtain the participants. In-depth interviews, using a semi-structured interview guide, were used to collect data. Audio-recorded data were transcribed, translated, and analysed using qualitative content analysis. Results Parents experienced difficulties in handling the children whose level of functioning was impaired due to abnormal and disruptive behaviour such as not being able to follow parental instructions. Psychological problems were also experienced due to caring demands exacerbated by lack of support and stigma from the community. Moreover, there were disruptions in family functioning and social interactions among family members due to the children’s behaviour. Lastly, too much time and family resources spent to fulfil the needs of these children culminated into disruption in economic activities that negatively affected everyday life. Conclusion Parents struggle to meet and cope with care demands posed by children with ADHD. The disruptive nature of ADHD symptoms presents a unique caring challenge different from those experienced with other childhood mental illnesses. To address these challenges, a collaborative approach among key stakeholders such as the government, health care professionals, and non-governmental organizations, is needed.